Attitude toward, acceptance of and knowledge about female sterilization as a method of contraception. (February 2015) - Erlenwein, J.; Kundu, S.; Schippert, C.; Soergel, P.; Hillemanns, P.; Staboulidou, I.
Abstract: Objective: Surgical sterilization via tubal ligation or the disconnection of the tubes is a method of permanent contraception. The aim of this study was to evaluate the attitude, acceptance and knowledge of women about female sterilization as a method of contraception in terms of the social and cultural backgrounds of those women. Study design: Prospective study based on an anonymous questionnaire that analyzed background knowledge, attitude, influence factors and motivation regarding sterilization, as well as the reasons for declining. The questionnaire also attempted to evaluate the effects on the self-esteem of the women, as well as the impact of religious dogma and the related beliefs. Results: One thousand, eight hundred questionnaires were distributed, and 1247 women completed the questionnaire—a response rate of 69.3%. There were mainly positive attitudes toward sterilization as a contraceptive method. Cultural background, including religion and faith; the mother's experiences and point of view; knowledge; family planning and the actual life situation have an influence on the attitudes toward and acceptance of sterilization as a contraceptive method and on the final choice of a contraceptive method. Conclusion: Cultural background and present life situation have a great impact on the attitude toward and acceptance of sterilization as a method of contraception, thus influencing the final choice of a contraceptive method. Detailed counselling about this topic is essential and should be improved.